Rancang Bangun Aplikasi Diagnosis Penyakit Hepatitis Menggunakan Certainty Factor - Pramana, Erista; Wurijanto, Tutut; Lemantara, Julianto (Jurnal JSIKA, 2012)
The World Health Organization (WHO) estimates that more than two billion people are infected with hepatitis B with a mortality rate of 250 thousand people per year and 170 million people worldwide suffer from hepatitis C with a death rate of 350 thousand people per year. The number of hepatitis patients in Indonesia is estimated that as many as 30 million people suffer from chronic hepatitis B and C. Half of it is thought to have chronic liver disease, with 10 percent of them become cancerous liver.Applications built will be able to help people with hepatitis in diagnosing and providing information about the disease hepatitis experienced. Information generated application form hepatitis outbreak confidence level based on the physical symptoms experienced were calculated using the Certainty Factor.Based on the evaluation of the test results, hepatitis disease diagnosis applications using Certainty Factor has been made capable of diagnosing hepatitis disease experienced by patients and give certainty to the illness as well as generate data that contains the results of diagnosis and disease therapy diet meal plan that can help the user provide solutions to the disease suffered hepatitis.   Keywords: WHO, Hepatitis, Certainty Factor, Evident, Diagnosis